KEPEMIMPINAN PEREMPUAN DALAM HIKAYAT PUTI BALQIS : TELAAH FILOLOGI DAN ANALISIS NILAI - Nofrizal, Nofrizal (STAI ALHIKMAH Jakarta, 2024)
AbstractLeadership is a factual theme that is always interesting to discuss throughout the history of mankind. This research uses Hikayat Puti Balqis, a manuscript originating from Surau Simaung, Sijunjung Regency, West Sumatra Province, as the object and primary source. The focus of this research is to explore the leadership values possessed by the main character in the Hikayat Puti Balqis. This research aims to describe the physical condition of the manuscript codicologically, present text edits through the critical edition method, and reveal the content of the text related to women's leadership that is still relevant today. The philological approach is used to ensure the authenticity and accuracy of the text presentation, while content analysis is applied to interpret leadership values in cultural and religious contexts. The results show that the Hikayat Puti Balqis contains four main leadership characteristics - a leader with great influence and charisma, a leader who is democratic and inclusive, a leader who is concerned about the safety of his people, and a leader who is intelligent and conscientious - and two key leadership values: wise, and diplomatic and peace-loving. This research offers a new perspective in understanding women's leadership values in the context of Islam and Malay culture. The findings not only enrich philological studies but also make a significant contribution to contemporary discussions on gender and leadership, particularly in the Islamic world and Southeast Asia. AbstrakKepemimpinan merupakan tema faktual yang selalu menarik untuk dibahas sepanjang sejarah umat manusia. Penelitian ini menggunakan Hikayat Puti Balqis, naskah yang berasal dari Surau Simaung, Kabupaten Sijunjung, Provinsi Sumatera Barat, sebagai objek dan sumber primer. Fokus penelitian ini adalah menggali nilai-nilai kepemimpinan yang dimiliki oleh tokoh utama dalam Hikayat Puti Balqis. Penelitian ini bertujuan untuk mendeskripsikan kondisi fisik naskah secara kodikologis, menyajikan suntingan teks melalui metode edisi kritis, serta mengungkap isi teks terkait kepemimpinan perempuan yang masih relevan hingga saat ini. Pendekatan filologi digunakan untuk memastikan otentisitas dan akurasi penyajian teks, sementara analisis isi diterapkan untuk menginterpretasikan nilai-nilai kepemimpinan dalam konteks budaya dan agama. Hasil penelitian menunjukkan bahwa Hikayat Puti Balqis memuat empat karakteristik kepemimpinan utama - yaitu pemimpin yang memiliki pengaruh besar dan kharisma, pemimpin yang demokratis dan inklusif, pemimpin yang memperhatikan keselamatan rakyatnya, serta pemimpin yang cerdas dan teliti - dan dua nilai kepemimpinan kunci: arif bijaksana, serta diplomatis dan cinta damai. Penelitian ini menawarkan perspektif baru dalam memahami nilai-nilai kepemimpinan perempuan dalam konteks Islam dan budaya Melayu. Temuan ini tidak hanya memperkaya kajian filologi tetapi juga memberikan kontribusi signifikan terhadap diskusi kontemporer tentang gender dan kepemimpinan, khususnya di dunia Islam dan Asia Tenggara.